Factor X Re-source - Designing the Recycling Society - Angrick, Michael.; Burger, Andreas.; Lehmann, Harry. (Eco-Efficiency in Industry and Science,, 2013)
Factor X: Re-source<U+0014>Designing the Recycling Society examines the issue of resources and raw materials, from the perspective of sustaining industrialized economies in the face of global competition for shrinking supplies. Although Germany has reduced its appetite for raw materials from some 680 tonnes per million GDP in 2000 to 580 tonnes in 2008, it still is not on track to meet the goals of its national sustainability strategy. Economical use of raw materials not only reduces pressure on the environment but also opens up economic opportunities for individual companies and the economy as a whole, as shown by a modeling study carried out on behalf of the German Federal Environment Agency. The role of recycling management is a key point in this work. This implies that rich industrialised countries will need to reduce their excessive consumption while other countries should be allowed to increase consumption. Human economies must meet each other in a <U+001c>sustainability corridor . Factor X: Re-source<U+0014>Designing the Recycling Society explores the role of recycling in efforts to achieve the sustainable world envisioned in the Federal Environment Ministry<U+0019>s Resource Efficiency Programme, known as ProgRess. The chapters build a roadmap to a Recycling Society in which the decoupling of resource consumption and economic growth is accomplished.